IMPLEMENTATION OF THE NURSING PROCESS IN PATIENT CARE AMONG NURSING STUDENTS AT THANG LONG UNIVERSITY AND ASSOCIATED FACTORS. (Vietnam Journal of Community Medicine, 2026)
Objective: 1) To describe the barriers to the implementation of the nursing process in patient care among nursing students of Thang Long University; (2) To analyze selected factors associated with the barriers to implementing the nursing process in patient care among the study participants.Methods: A cross-sectional descriptive study was conducted on all 232 nursing students enrolled in the master’s program and the bridging program from college to university at Thang Long University from January to August 2025. The barrier assessment instrument was adapted from the study by Manal Hamed Mahmoud, which demonstrated a Cronbach’s alpha of 0.820. Data were collected through interviewer-administered questionnaires and subsequently entered and analyzed using SPSS version 20.0.Results: Overall, 43.1% of students reported barriers, while 56.9% rated no barriers. The main barriers to implementing the nursing process identified by students included a lack of experience and ongoing training, high workload, staff shortages, non-care-related administrative burden, insufficient equipment and documentation forms, and time and funding constraints. In addition, management-related limitations were noted, including a lack of support and supervision, as well as hospital regulations and legal documents. Several factors were statistically associated with barriers in nursing process practice. Male students experienced more barriers than females (OR = 2.40; p < 0.001). Students from Internal Medicine/Pediatrics (OR = 3.08; p < 0.001) and Surgery/Obstetrics (OR = 2.37; p < 0.05) had a lower prevalence of barriers compared with those from other/specialty departments. Moreover, students in the master’s program reported more barriers than those in the undergraduate group (OR = 2.03; p